Android-Based Monitoring of 110 Volt DC System in Substations within PLN UIT JBM Region to Improve Maintenance Efficiency - Erwin Dhaniswara; Nurholis Nurholis; Tamaji Tamaji (Journal of Electrical Engineering and Computer (JEECOM), 2025)
The DC 110 Volt system is a critical component in substations, serving to support the operation of control and protection devices. Instability in voltage or current within this system can result in serious failures in overall substation performance. Therefore, “Monitoring of the DC 110 Volt System in Substations within PLN UIT JBM Region Based on Android to Improve Maintenance Efficiency” in real time becomes crucial. This research aims to design and implement an Android-based monitoring system supported by Internet of Things (IoT) technology using the Blynk application. The main parameters monitored in the DC system are total DC voltage (positive and negative) within a range of 80–125 VDC and current within a range of 0–100 A, integrated with a microcontroller that transmits data to the Android application via data communication protocols. The data received by the application can be analyzed in real time, providing critical information regarding parameter deviations from operational standards. In addition, the system is equipped with an early warning feature that enables technicians to respond to potential disturbances before they affect substation operations. Based on sampling inspections of the DC system conducted by five personnel at five substations within the PLN UIT JBM region, the results show that using the DC monitoring system is more effective than manual measurements, with a time difference of 10–15 minutes. This demonstrates that the system can improve monitoring efficiency and reduce operational risks in substations. With the application of this technology, disturbances in the DC system can be detected earlier, allowing preventive actions to be carried out quickly and accurately.